Control of ferroelectric and linear piezoelectric response of PZT films through texture. Issue 7 (24th January 2018) - Das, Debashish; Sanchez, Luz; Martin, Joel; Power, Brian; Isaacson, Steven; Polcawich, Ronald G.; Chasiotis, Ioannis
Abstract: The high and low field ferroelectric response of freestanding PbZr0.52 Ti0.48 O3 (PZT) films, with texture varying from 100% (001) to 100% (111) was investigated via 500 nm thick PZT unimorphs deposited on the same substrate. It is shown that the ferroelectric and piezoelectric properties depend strongly on texture, and the effective transverse strain and stress coefficients vary linearly with %(001) and %(111) texture factors. PZT films with 100% (001) orientation displayed 150%, 140%, and 80% larger linear piezoelectric strain coefficient, saturated strain coefficient, and saturated stress coefficient, respectively, compared to films with 100% (111) orientation. As a result, pure (001) textured PZT films with 20% higher dielectric constant have 50% higher figure of merit in sensing than films with pure (111) texture. The piezoelectric and ferroelectric properties of all but one combinations of (001) and (111) texture were shown for the first time to be bounded by the values for 100% (001) and 100% (111) texture. A notable exception was PZT films comprised of 73% (001) and 27% (111) texture which showed stable piezoelectric coefficients at all electric fields, with major technological implication to low power microdevices. Finally, the coercive field was shown to decrease with (001) texture factor and excess‐Pb in the PZT and the PbTiO3 seed layer.